2017
DOI: 10.1007/s10064-017-1068-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 3D structural model of a mine by consolidating different data sources

Abstract: Joints and faults are inherent part of the rock mass. In the vast majority of mining slopes, discontinuity structures play an important role in slope stability and may trigger a slope failure. The most important step in understanding the slope failure mechanism is to have a reliable model, which shows how all the discontinuity sets are constituted in the rock mass and how they interact with each other. However, building a fracture model is not a straightforward process, since it needs to combine discontinuity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…In terms of joint persistence, zone 2 is believed to be enclosed by two clay filled water barriers related to FS3. Average spacing between the main fractures of lineament FS3 is around 400-500 meters (Morales et al, 2017a), which is the widest spacing of all the fracture systems at this mine. Radar monitoring of the area confirms small displacements of a well monitored wedge during rainfall events.…”
Section: Hydraulic Conductivity Assessmentmentioning
confidence: 87%
See 3 more Smart Citations
“…In terms of joint persistence, zone 2 is believed to be enclosed by two clay filled water barriers related to FS3. Average spacing between the main fractures of lineament FS3 is around 400-500 meters (Morales et al, 2017a), which is the widest spacing of all the fracture systems at this mine. Radar monitoring of the area confirms small displacements of a well monitored wedge during rainfall events.…”
Section: Hydraulic Conductivity Assessmentmentioning
confidence: 87%
“…Discontinuities like faults, joints or cracks developed generally due to tectonic activities provide important clue on surface features and are responsible for infiltration of surface run off into sub-surface and also for movement and storage of groundwater (Subbu Rao et al, 2001). Morales et al (2017a) have shown that there are six different main discontinuities orientations in the mine area, which are correlated with the regional pattern of lineaments. In this manner it was also possible to distinguish six different fracture systems (FS) in the site, as shown in Figure 1.…”
Section: Lineamentsmentioning
confidence: 87%
See 2 more Smart Citations
“…In mining operations, the precise determinations of relevant fault geometries oriented to geotechnical design are a major concern for structural geologists and geotechnical engineers [1][2][3][4][5]. The principal uncertainties in structural and geomechanical models are mainly controlled by both limited data collection resolution [6] as well as the spatial distribution of data.…”
Section: Introductionmentioning
confidence: 99%